Anatomical and histological characteristics of the hepatobiliary system in adult Sox17 heterozygote mice. Issue 12 (2nd July 2020) - Pattarapanawan, Montri; Uemura, Mami; Miyazaki, Nanae; Takami, Shohei; Tomiyasu, Hirotaka; Tsunekawa, Naoki; Hirate, Yoshikazu; Fujishiro, Jun; Kurohmaru, Masamichi; Kanai‐Azuma, Masami; Higashiyama, Hiroki; Kanai, Yoshiakira
Abstract: Biliary atresia (BA) is a rare neonatal disease characterized by inflammation and obstruction of the extrahepatic bile ducts (EHBDs). The Sox17‐ haploinsufficient ( Sox17 +/− ) mouse is an animal model of BA that encompasses bile duct injury and subsequent BA‐like inflammation by the neonatal stage. Most Sox17 +/− neonates die soon after birth, but some Sox17 +/− pups reach adulthood and have a normal life span, unlike human BA. However, the phenotype and BA‐derived scars in the hepatobiliary organs of surviving Sox17 +/− mice are unknown. Here, we examined the phenotypes of the hepatobiliary organs in post‐weaning and young adult Sox17 +/− mice. The results confirmed the significant reduction in liver weight, together with peripheral calcinosis and aberrant vasculature in the hepatic lobule, in surviving Sox17 +/− mice as compared with their wild‐type (WT) littermates. Such hepatic phenotypes may be sequelae of hepatobiliary damage at the fetal and neonatal stages, a notion supported by the slight, but significant, increases in the levels of serum markers of liver damage in adult Sox17 +/− mice. The surviving Sox17 +/− mice had a shorter gallbladder in which ectopic hepatic ducts were more frequent compared to WT mice. Also, the surviving Sox17 +/− mice showed neither obstruction of the EHBDs nor atrophy or inflammation of hepatocytes or the intrahepatic ducts. These data suggest that some Sox17 +/− pups with BA naturally escape lethality and recover from fetal hepatobiliary damages during the perinatal period, highlighting the usefulness of the in vivo model in understanding the hepatobiliary healing processes after surgical restoration of bile flow in human BA.